Individual Effective Dose and Nuclear Emergency Planning for Muntok NPP Area using TMI-2 Source Term - Sunarko Sunarko; Zaki Su'ud (Jurnal Pengembangan Energi Nuklir, 2020)
Probabilistic dose analysis from a postulated nuclear accident is performed for the Muntok area in the western Bangka region. Three-Mile Island unit 2PWR-type Nuclear Power Plant (TMI-2) source-term is compiled and used as accident data. The accident is also known as the Small-break Loss of Coolant Accident (SB-LOCA) accident. The isotopes used in the simulation are Kr-88, I-131, Xe-133, and Cs-137. The release point is a 50 m stack. Lagrangian particle dispersion method (LPDM) is used along with a 3-dimensional mass-consistent wind-field. Surface-level time-integrated air concentration and spatial distribution of ground-level total dose were obtained for dry conditions. Meteorological data is taken from hourly records obtained from an on-site meteorological tower in Muntok area for the 2014-2015 period. Effluent is released at a uniform rate during a 6-hour period and the dose is integrated for 12 hours from the beginning of the release until most of the plume left the model boundaries. The regulatory limit for the general public of 1 mSv was detected in an area located 2.5 km from the release point. Radioactive plume is spread from the postulated plant location to uninhabited areas consisted of bushes and farming areas in the SE-SSE direction and to W-NW direction to the Bangka Sea.